The Emerging Role of microRNAs in Polyglutamine Diseases - Dong, Xiaoyu; Cong, Shuyan (Frontiers in Molecular Neuroscience, 2019)
MicroRNAs (miRNAs) are small non-coding molecules that regulate a large amount of post-transcriptional repressor genes by recognizing semi-complementary target sequences that are normally located in the 3′ UTR of the mRNA. Altered expression of miRNA has been related to several pathological processes, including polyglutamine (Poly Q) diseases. Specific expression patterns in the circulating fluids and brain parenchyma have been speculated as potential biomarkers for Poly Q disease diagnosis and prognosis. Several miRNAs have been consistently identified in diseases including Huntington’s disease (HD) and spinocerebellar ataxia (SCA). In our review, we describe the emerging role of miRNAs in Poly Q diseases and provide an overview on general miRNA biology, implications in pathophysiology, and their potential roles as future biomarkers and applications for therapy.